A Bibliometric Research in Telugu Literature in University of Hyderabad, India - Ali, Yakub; Varatharajan, N.; Sarangapani, R. (An Overview of Literature, Language and Education Research Vol. 2, 2024)
The main objective of the Telugu department is to promote the studies in Telugu language and literature. It undertakes teaching and research in Telugu with emphasis on various aspects of historical and comparative studies in Telugu language and literature. Bibliometric is the method of statistical analysis of written communications such as books, journal articles, theses and dissertations, etc. These methods are frequently used in the field of library and Information Science with the purpose of providing a quantitative analysis of academic literature. The data collected, tabulated and percentages were calculated for the study. It is found that a total of 234 dissertations have been submitted to the Telugu Department, University of Hyderabad for an award of M.Phil. degrees during the study period i.e. 2000 to 2014. During the years 2013 and 2014, comparatively, more dissertations i.e. 22 (9.40%) have been submitted and ranked I, and also found after gender analysis, that 75% i.e. 175 dissertations have been submitted by the male research scholars. The faculty members who supervised the research work have also been studied and presented. The Telugu department of the University of Hyderabad is contributing new knowledge in the field of Telugu language and literature by conducting research.